GOOD CORPORATE GOVERNANCE, GREEN ACCOUNTING, AND EARNINGS SUSTAINABILITY: EVIDENCE FROM JAKARTA ISLAMIC INDEX - Rokhaniyah, Siti; Khotijah, Siti Afidatul; Manurung, Herlina; Permatasari, Desi; Anisyawati, Anisyawati (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2024)
This research examines the  influence of good corporate governance  (GCG) practices  on  the earnings sustainability of  companies listed  in  the Jakarta Islamic Index.  Additionally, it explores the role of green accounting in the relationship between GCG and  sustainable earnings.  GCG is represented by management ownership,  boards of commissioners,  the  audit  committee,  and institutional ownership.  Green accounting is measured  using the corporate environmental management  (PROPER) results,  which  are aligned with the regulations of the  Ministry  of Environment and Forestry of Indonesia. Data analysis was carried out using panel data regression  analysis.  The findings indicate that GCG components (management  ownership, boards of commissioners, and audit committee) positively  impact sustainable earnings.  Moreover, green accounting has been empirically proven to moderate the positive effect of GCS on sustainable earnings.  Based on the sustainability theory, companies tend to undertake ethical and legal measures to achieve sustainable performance. Thus, sustainability theory suggests that the synergy between corporate governance and green accounting may improve earnings sustainability.JEL: M14, M41, L25.